Modern Historico-Pedagogical Literature on Kharkiv University Activities in the 19th-early 20th century - Kulysh, S.M. (My University, 2016)
У статті з історико-педагогічної точки зору аналізується наукова література 90-х рр. ХХ ст. – початку ХХІ ст., присвячена діяльності Харківського університету дореволюційної епохи, подальшого розвитку педагогічної науки, суттєвого поліпшення системи підготовки науково-педагогічних кадрів, втіленню до навчального процесу методичних новацій. В статье с историко-педагогической точки зрения анализируется научная литература 90-х г. ХХ ст. – начало ХХІ ст., посвященная деятельности Харьковского университета дореволюционной эпохи, дальнейшему развитию педагогической науки, существенному улучшению системы подготовки научно-педагогических кадров, внедрению методических новаций. The article provides historical and pedagogical viewpoint on scientific literature ranging from the 1990-s to the beginning of the 21 century dedicated to the activity of Kharkiv University before the revolution, further development of pedagogics, considerable improvement in scientific and pedagogical staff training, introduction of methodological innovations into pedagogical activity.
Keywords: історико-педагогічні науки; науково-педагогічні кадри; університет; методичні новації; историко-педагогические науки; научно-педагогические кадры; университет; методические новации; historical and pedagogical sciences; historical and pedagogical staff; methodological innovations; university